Evaluation Of The Implementation Environmentally Friendly Material Management In The Green Construction Concept - Muhammad Kaisar Diandra; Rani Gayatri Kusumawardhani (Green Publisher Indonesia, 2025)
The rapid growth of Indonesia's construction industry has led to increased construction waste, excessive material consumption, and significant carbon emissions. Construction waste alone contributes up to 40% of total global waste, which, if not managed effectively, results in resource wastage, increased project costs, and environmental harm. This research evaluates the implementation of Green Construction principles during the construction phase of building projects in Indonesia, identifies factors hindering its implementation, and formulates strategic recommendations for improvement. The study adopts a mixed-method approach, combining quantitative analysis (Likert scale questionnaires of 1–4 based on indicators from the Ministry of Public Works and Housing Circular No. 1 of 2022 and the PUSKIM 2016 rating system) with qualitative analysis through in- depth interviews with project stakeholders. Three building projects with varying certification levels were analyzed: RS Harapan Kita–Tokushukai (LEED Platinum), RS Kanker Dharmais (Greenship Gold), and Labtek XV ITB (non-certified). Evaluation results indicated that RS Harapan Kita achieved the highest implementation level (average indicator score 3.4/4 or 85%), followed by RS Dharmais (2.8/4 or 70%), and Labtek XV ITB (2.2/4 or 55%). Major implementation barriers identified include weak governmental regulations, insufficient project management commitment, limited availability of certified green materials, and low adoption of digital monitoring technologies on-site. The study recommends strategies to strengthen regulations and government incentives, enhance digital technology utilization (such as BIM), optimize green supply chains, and increase human resource capacity. These findings provide practical input for improving sustainable construction practices in Indonesian building projects.